A Randomized Multiple Micronutrient Powder Point-of-Use Fortification Trial Implemented in Indian Preschools Increases Expressive Language and Reduces Anemia and Iron Deficiency. Issue 7 (20th April 2021) - Black, Maureen M; Fernandez-Rao, Sylvia; Nair, Krishnapillai Madhavan; Balakrishna, Nagalla; Tilton, Nicholas; Radhakrishna, Kankipati Vijaya; Ravinder, Punjal; Harding, Kimberly B; Reinhart, Gregory; Yimgang, Doris P; Hurley, Kristen M
ABSTRACT: Background: Anemia is a global public health problem that undermines childhood development. India provides government-sponsored integrated nutrition/child development preschools. Objectives: This double-masked, cluster-randomized controlled trial examines whether point-of-use multiple micronutrient powder (MNP) compared with placebo fortification of preschool meals impacts child development and whether effects vary by preschool quality (primary outcome) and biomarkers of anemia and micronutrients (secondary outcomes). We also measured growth and morbidity. Methods: We randomly assigned 22 preschools in rural India to receive MNP/placebo fortification. We administered baseline and endline blood sampling and measures of childhood development (Mullen Scales of Early Learning, inhibitory control, social–emotional), anthropometry, and morbidity to preschoolers (aged 29–49 mo). Preschools added MNP/placebo to meals 6 d/wk for 8 mo. We conducted linear mixed-effects regression models accounting for preschool clustering and repeated measures. We evaluated child development, examining effects in high- compared with low-quality preschools using the Early Childhood Environment Rating Scale–Revised and the Home Observation for the Measurement of the Environment Inventory, modified for preschools. Results: At baseline, mean age ± SD was 36.6 ± 5.7 mo, with 47.8% anemic, 41.9% stunted, and 20.0% wasted. Baseline expressive/receptive language scores were higher in high-quality compared with low-quality preschools ( P  = 0.02 and P  = 0.03, respectively). At endline (91% retention, n  = 293/321), we found MNP compared with placebo effects in expressive language (Cohen's standardized effect d  = 0.4), inhibitory control ( d  = 0.2), and social–emotional ( d  = 0.3) in low-quality, not high-quality, preschools. MNP had significantly greater reduction of anemia and iron deficiency compared with placebo (37% compared with 13.5% and 41% compared with 1.2%, respectively). There were no effects on growth or morbidity. Conclusions: Providing multiple micronutrient-fortified meals in government-sponsored preschools is feasible; reduced anemia and iron deficiency; and, in low-quality preschools, increased preschoolers' expressive language and inhibitory control and reduced developmental disparities. Improving overall preschool quality by incorporating multiple components of nurturing care (responsive care, learning, and nutrition) may be necessary to enhance preschoolers' development. This trial was registered at clinicaltrials.gov as NCT01660958.